Hot Nasal Packing With Hot Saline Irrigation for Hemostasis After Adenoidectomy: a Prospective Randomized Controlled Study - Ceylan, Seyit Mehmet; Sezgin, Efe; Dişikırık, İlyas; Kanmaz, Mahmut Alper; Yıldırım, Alton; Sezgin, Efe (Elsevier, 2020)
Objective: This study aimed to investigate the efficacy of hot posterior nasal packing and hot saline irrigation in bleeding control after adenoidectomy. Methods: A total of 130 patients scheduled for adenoidectomy were included in the study, and randomized into two groups at the beginning of the surgical operation. After adenoidectomy, saline impregnated tampon, and saline irrigation at room temperature (22 degrees C) was applied to the patients in one group while 50 degrees C saline impregnated tampon and saline irrigation at the same temperature were applied to the patients in the other group. We recorded hemostasis for up to 3 min after tamponade for bleeding control, and the amount of bleeding into the nasopharynx. Results: The age of the patients ranged from 1.5 to 13 years (mean +/- SD: 6.07 +/- 3.08 years, and 5.33 +/- 2.55 years, 22 degrees C and 50 degrees C saline irrigation groups, respectively). There were 37 males and 28 females in the 22 degrees C saline group, while 34 males and 31 females in the 50 degrees C saline group. When comparing the two groups, there was no statistically significant difference in terms of duration of hemostasis (p = 0.64). However, bleeding scores at 2 nd min after the tamponade were significantly lower in the 50 degrees C saline group (p = 0.007). The amount of bleeding in the 50 degrees C saline group was also significantly lower than the 22 degrees C saline group (p = 0.015). Conclusion: In this study, application of 50 degrees C saline impregnated tampon, and hot saline irrigation was found to be more effective in the control of bleeding after adenoidectomy by reducing the amount of bleeding compared to 22 degrees C saline impregnated tampon application and saline irrigation at 22 degrees C. However, hot nasal packing and hot saline irrigation did not affect duration of hemostasis and cauterization.
Keywords: Hot tampon; Hot saline; Adenoidectomy; Hemostasis; Bleeding control